ANALISIS KOMPARATIF TERHADAP LAPORAN KEUANGAN PT. HANJAYA MANDALA SAMPOERNA TBK - Siti Nur Hidayah; Martinus Robert Hutauruk; Mansyur (University of Widya Gama Mahakam Samarinda, 2020)
This research mothod is descriptive, the comparative method used is the ratio of liquidity to the current ratio, solvency in the debt to asset ratio, activity on total asset turn over and profitability on return on asset to determine the company’s financial performance. From the analysis it is known that the comparative balance sheet report from 2014 to 2018 that the financial position and income statement of PT. Hanjaya Mandala Sampoerna Tbk showed an increase. Liquidity ratio shows that the company’s performance is very good and the company is able to pay off its short-term financial obligations, the solvency ratio shown that the company’s performance is very good and the company is able to guarantee the debt payments given by the creditor, and is able to guarantee the debt given by the criditor of the assets owned, aktivity ratio shows that the company’s performance is very good and the company is able to generate good sales from overall asset mangement, & profitability ratios indicate that the company’s performance is very good and the company is able to generate good profits from the assets used or from it’s own capital.